Credit union policies and performance in Latin America - Westley, Glenn D.; Shaffer, Sherrill (Journal of Banking & Finance, 1999)
This paper explores empirical linkages between credit unions’ (CUs’) policies and their financial performance, as measured by loan delinquency and profitability, using a unique micro dataset of credit unions in three Latin American countries. The estimated translog profit function is generalized using a slack variable concept that parameterizes any systematic deviation from profit-maximizing behavior exhibited within the sample. In general, we find that performance depends in important ways on two types of CU policy variables, some associated with the incentives of borrowers to repay and others that affect the CU’s ability to screen loans.